Current‐voltage relation for the Saturnian system. Issue 6 (19th June 2013) - Ray, L. C.; Galand, M.; Delamere, P. A.; Fleshman, B. L.
Abstract : [1] Saturn's magnetosphere is populated by plasma created from neutrals ejected by the moon Enceladus. These neutrals are ionized and picked up by the planetary magnetic field requiring large amounts of angular momentum to be transferred from Saturn's upper atmosphere to the magnetospheric plasma. The resulting upward currents that supply this angular momentum are associated with electrons, which travel toward the planetary atmosphere. At high magnetic latitudes along the flux tube, parallel electric fields may develop to enhance the field‐aligned current density flowing between the two regions. We show that, similar to the Jovian system, the current‐voltage relation in the Saturnian system must be evaluated at the top of the acceleration region, which occurs at ~1.5 R S along the magnetic field line as measured from the center of the planet. Owing to the large abundance of protons in the Saturnian system, cold electrons carry the majority of the field‐aligned current for net potential drops less than 500 V. For the flux tube intersecting the equatorial plane at 4 R S, field‐aligned potentials of 50–130 V are consistent with the energy fluxes inferred from the Enceladus emission. In the middle magnetosphere, field‐aligned potentials of ∼1.5 kV produce ionospheric electron energy fluxes of 0.3 mW/m 2 when hot electrons comprise 0.3% of the magnetospheric electron population. Key Points: Current‐voltage relation must be evaluated at high magnetic latitudes. Cold electrons contribute strongly to field‐aligned current density. Full Knight (1973) current‐voltage relation must be applied to Saturnian system.